2022
DOI: 10.1021/acs.biomac.2c00132
|View full text |Cite
|
Sign up to set email alerts
|

Pro-angiogenic Potential of Mesenchymal Stromal Cells Regulated by Matrix Stiffness and Anisotropy Mimicking Right Ventricles

Abstract: Capillary rarefaction is a hallmark of right ventricle (RV) failure. Mesenchymal stromal cell (MSC)-based therapy offers a potential treatment due to its pro-angiogenic function. However, the impact of RV tissue mechanics on MSC behavior is unclear, especially when referring to RV end-diastolic stiffness and mechanical anisotropy. In this study, we assessed MSC behavior on electrospun scaffolds with varied stiffness (normal vs failing RV) and anisotropy (isotropic vs anisotropic). In individual MSCs, we observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…We recently reported different MSC responses to varied matrix stiffness and anisotropy degrees using PEUU scaffolds mimicking healthy and diseased right ventricles. The biaxial elastic behavior was measured in the main fiber and cross-fiber directions, and anisotropic elastic behavior was confirmed [97]. A re-examination of the two anisotropic scaffold groups that represent healthy (soft) and diseased (stiff) right ventricle elasticities was performed via stress relaxation tests.…”
Section: Limitations Of Current Viscoelastic Scaffoldsmentioning
confidence: 89%
See 2 more Smart Citations
“…We recently reported different MSC responses to varied matrix stiffness and anisotropy degrees using PEUU scaffolds mimicking healthy and diseased right ventricles. The biaxial elastic behavior was measured in the main fiber and cross-fiber directions, and anisotropic elastic behavior was confirmed [97]. A re-examination of the two anisotropic scaffold groups that represent healthy (soft) and diseased (stiff) right ventricle elasticities was performed via stress relaxation tests.…”
Section: Limitations Of Current Viscoelastic Scaffoldsmentioning
confidence: 89%
“…Matrix anisotropy has been shown to play a role in MSC morphology, differentiation fate, and other paracrine functions [110][111][112][113][114][115][116]. Recently, Nguyen-Truong et al [97] examined the effect of RV tissue mechanics on the pro-angiogenic paracrine function of MSCs, concentrating on the combined effect of RV-like tissue stiffness and anisotropy. Using random and aligned PEUU electrospun scaffolds with the stiffness of normal RVs, they found that the MSCs cultured on the anisotropic group consistently exhibited a higher pro-angiogenic function than those cultured on the isotropic group, showing a positive influence of anisotropy on MSC paracrine function.…”
Section: Cell-level Impact Of Substrate Anisotropymentioning
confidence: 99%
See 1 more Smart Citation